Opportunities for mitigating net system greenhouse gas emissions in Southeast Asian rice production: A systematic review - Zhang, Zhenglin; Macedo, Ignacio; Linquist, Bruce A.; Sander, Bjoern Ole; Pittelkow, Cameron M. (Elsevier, 2024)
Southeast Asia (SEA) is a key producer and exporter of rice, accounting for around 28% of rice produced globally. To effectively mitigate greenhouse gas (GHG) emissions in SEA rice systems, field methane (CH4) and nitrous oxide (N2O) emissions have been intensively studied. However, an integrated assessment of system-level GHG emissions which includes other carbon (C) balance components, such as soil organic carbon (SOC) or energy use, that can positively or negatively influence the net capacity for climate change mitigation is lacking. We conducted a systematic review of published research in SEA rice systems to synthesize findings across four main components of net system emissions: (1) field GHG emissions, (2) energy inputs, (3) residue utilization beyond the field, and (4) SOC change. The objectives were to highlight effective mitigation opportunities and explore cross-component effects to identify tradeoffs and key knowledge gaps. Field GHG emissions were the largest contributor to net system emissions in agreement with existing scientific consensus, with results showing that practices such as floodwater drainage and residue removal are sound options for CH4 mitigation. On the other hand, increasing SOC potentially provides a large GHG mitigation opportunity, with long-term continuous rice cropping and practices such as residue incorporation and biochar application promoting SOC increase. A reduction in energy inputs was mainly achieved by optimizing agrochemical use, especially N fertilizers. For residue utilization beyond the field, GHG emission mitigation mainly came from preventing open field burning through residue removal. Removed residue can subsequently be used for producing energy that offsets GHG emissions associated with conventional fuel sources (e.g. fossil fuel-based electricity generation) or substituting material used in other production systems. Integrating all four components of net system emissions into one analysis underscores the following two main takeaways. First, the components of field GHG emissions and SOC change are the biggest opportunities for reducing net system emissions and need to be considered for effective climate change mitigation. Second, the reduction of C inputs through residue removal and increased soil aeration through multiple drainage will lower CH4 emissions but may also potentially decrease SOC stocks over time. Hence, we argue that future research needs to consider cross-component effects to optimize net system emissions, specifically the “stacking” of best management practices for mitigation related to field GHG emissions or SOC change in long-term experiments.